Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the given system of simultaneous equations:
1. [tex]\[\frac{x+1}{3}+\frac{y}{2}=0\][/tex]
2. [tex]\[\frac{x}{2}-2=\frac{y-1}{3}\][/tex]
we will go through a step-by-step procedure to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex].
### Step 1: Clear the Fractions
First, let's eliminate fractions by multiplying each equation by the least common multiple (LCM) of the denominators.
Equation 1:
[tex]\[ \frac{x+1}{3} + \frac{y}{2} = 0 \][/tex]
The LCM of 3 and 2 is 6. Multiply the entire equation by 6:
[tex]\[6 \left(\frac{x+1}{3}\right) + 6 \left(\frac{y}{2}\right) = 6 \cdot 0 \][/tex]
Simplifying:
[tex]\[2(x+1) + 3y = 0\][/tex]
[tex]\[2x + 2 + 3y = 0\][/tex]
Rewriting it:
[tex]\[2x + 3y = -2 \quad \text{(Equation 3)}\][/tex]
Equation 2:
[tex]\[ \frac{x}{2} - 2 = \frac{y-1}{3} \][/tex]
The LCM of 2 and 3 is 6. Multiply the entire equation by 6:
[tex]\[6 \left(\frac{x}{2}\right) - 6 \cdot 2 = 6 \left(\frac{y-1}{3}\right)\][/tex]
Simplifying:
[tex]\[3x - 12 = 2(y - 1)\][/tex]
[tex]\[3x - 12 = 2y - 2\][/tex]
Rewriting it:
[tex]\[3x - 2y = 10 \quad \text{(Equation 4)}\][/tex]
### Step 2: Solve the System of Linear Equations
Now we have the system of equations:
1. [tex]\(2x + 3y = -2\)[/tex]
2. [tex]\(3x - 2y = 10\)[/tex]
We can use the method of elimination or substitution to solve for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]. Let's use elimination:
Elimination Method:
To eliminate [tex]\(y\)[/tex], let's multiply Equation 3 by 2 and Equation 4 by 3 to make the coefficients of [tex]\(y\)[/tex] equal:
Multiply Equation 3 by 2:
[tex]\[4x + 6y = -4 \quad \text{(Equation 5)}\][/tex]
Multiply Equation 4 by 3:
[tex]\[9x - 6y = 30 \quad \text{(Equation 6)}\][/tex]
Add Equation 5 and Equation 6:
[tex]\[ (4x + 6y) + (9x - 6y) = -4 + 30 \][/tex]
[tex]\[ 4x + 9x + 6y - 6y = 26 \][/tex]
[tex]\[ 13x = 26 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{26}{13} \][/tex]
[tex]\[ x = 2 \][/tex]
### Step 3: Substitute [tex]\(x\)[/tex] Back to Find [tex]\(y\)[/tex]
Now substitute [tex]\(x = 2\)[/tex] back into one of the original equations to find [tex]\(y\)[/tex]. We'll use Equation 3:
[tex]\[2(2) + 3y = -2\][/tex]
[tex]\[4 + 3y = -2\][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[3y = -2 - 4\][/tex]
[tex]\[3y = -6\][/tex]
[tex]\[y = \frac{-6}{3}\][/tex]
[tex]\[y = -2\][/tex]
### Conclusion
The solution to the system of equations is:
[tex]\[ x = 2, \quad y = -2 \][/tex]
1. [tex]\[\frac{x+1}{3}+\frac{y}{2}=0\][/tex]
2. [tex]\[\frac{x}{2}-2=\frac{y-1}{3}\][/tex]
we will go through a step-by-step procedure to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex].
### Step 1: Clear the Fractions
First, let's eliminate fractions by multiplying each equation by the least common multiple (LCM) of the denominators.
Equation 1:
[tex]\[ \frac{x+1}{3} + \frac{y}{2} = 0 \][/tex]
The LCM of 3 and 2 is 6. Multiply the entire equation by 6:
[tex]\[6 \left(\frac{x+1}{3}\right) + 6 \left(\frac{y}{2}\right) = 6 \cdot 0 \][/tex]
Simplifying:
[tex]\[2(x+1) + 3y = 0\][/tex]
[tex]\[2x + 2 + 3y = 0\][/tex]
Rewriting it:
[tex]\[2x + 3y = -2 \quad \text{(Equation 3)}\][/tex]
Equation 2:
[tex]\[ \frac{x}{2} - 2 = \frac{y-1}{3} \][/tex]
The LCM of 2 and 3 is 6. Multiply the entire equation by 6:
[tex]\[6 \left(\frac{x}{2}\right) - 6 \cdot 2 = 6 \left(\frac{y-1}{3}\right)\][/tex]
Simplifying:
[tex]\[3x - 12 = 2(y - 1)\][/tex]
[tex]\[3x - 12 = 2y - 2\][/tex]
Rewriting it:
[tex]\[3x - 2y = 10 \quad \text{(Equation 4)}\][/tex]
### Step 2: Solve the System of Linear Equations
Now we have the system of equations:
1. [tex]\(2x + 3y = -2\)[/tex]
2. [tex]\(3x - 2y = 10\)[/tex]
We can use the method of elimination or substitution to solve for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]. Let's use elimination:
Elimination Method:
To eliminate [tex]\(y\)[/tex], let's multiply Equation 3 by 2 and Equation 4 by 3 to make the coefficients of [tex]\(y\)[/tex] equal:
Multiply Equation 3 by 2:
[tex]\[4x + 6y = -4 \quad \text{(Equation 5)}\][/tex]
Multiply Equation 4 by 3:
[tex]\[9x - 6y = 30 \quad \text{(Equation 6)}\][/tex]
Add Equation 5 and Equation 6:
[tex]\[ (4x + 6y) + (9x - 6y) = -4 + 30 \][/tex]
[tex]\[ 4x + 9x + 6y - 6y = 26 \][/tex]
[tex]\[ 13x = 26 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{26}{13} \][/tex]
[tex]\[ x = 2 \][/tex]
### Step 3: Substitute [tex]\(x\)[/tex] Back to Find [tex]\(y\)[/tex]
Now substitute [tex]\(x = 2\)[/tex] back into one of the original equations to find [tex]\(y\)[/tex]. We'll use Equation 3:
[tex]\[2(2) + 3y = -2\][/tex]
[tex]\[4 + 3y = -2\][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[3y = -2 - 4\][/tex]
[tex]\[3y = -6\][/tex]
[tex]\[y = \frac{-6}{3}\][/tex]
[tex]\[y = -2\][/tex]
### Conclusion
The solution to the system of equations is:
[tex]\[ x = 2, \quad y = -2 \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.